2013
DOI: 10.4236/jbise.2013.68099
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stent porosity on the endovascular treatment of intracranial aneurysms located near a bifurcation

Abstract: Intracranial aneurysm occurs when a cerebral artery develops an abnormal sac-like dilatation, and will cause massive bleeding in the subarachnoid space upon rupture. Endovascular stenting is a minimally invasive procedure in which a flow-diverting stent is deployed to cover the aneurysm neck, thereby restricting blood from entering the aneurysm and reducing the risk of rupture. The stent porosity, a crucial factor determining the intra-aneurysmal hemodynamics f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Stent configuration, porosity, and position are all believed to be crucial determining factors of treatment efficacy [ 4 , 22 , 23 ]. In general, a stent with low porosity can reduce the flow entering the aneurysm substantially [ 23 , 24 ]. However, the flow dynamics associated with changing side branch vessel diameter was not analyzed quantitatively in these earlier works.…”
Section: Introductionmentioning
confidence: 99%
“…Stent configuration, porosity, and position are all believed to be crucial determining factors of treatment efficacy [ 4 , 22 , 23 ]. In general, a stent with low porosity can reduce the flow entering the aneurysm substantially [ 23 , 24 ]. However, the flow dynamics associated with changing side branch vessel diameter was not analyzed quantitatively in these earlier works.…”
Section: Introductionmentioning
confidence: 99%
“…2,20,24 In vitro studies have shown that the flow diverting effect is increased in devices with low porosity like FDs compared to high-porosity intracranial stents. 25,26 Moreover, a multicentre study of Wang et al detected that lower metal coverage is an independent risk factor for aneurysm recurrence that enables a more effective flow lamination by FD than multilayer stents. 27 Endovascular treatment by flow diversion is increasingly used in ruptured intracranial aneurysms, with lower mortality and morbidity compared to open surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that the flow diverting effect is increased in devices with low porosity like FDs compared to high-porosity intracranial stents. 25,26 Moreover, a multicentre study of Wang et al. detected that lower metal coverage is an independent risk factor for aneurysm recurrence that enables a more effective flow lamination by FD than multilayer stents.…”
Section: Discussionmentioning
confidence: 99%
“…For coronary artery, the flow rate (∼2.35 ml/s) is generally higher [24]. For brain aneurysm, the flow rate (∼0.03 ml/s) is generally lower [25]. The flow rates can be adjusted by changing the pressing condition of the impedance pump, the position of pressing site relative to the elastic tube and the ID of the flow loop.…”
Section: Discussionmentioning
confidence: 99%